Probing the role of the residues in the active site of the transaminase from Thermobaculum terrenum. - Ekaterina Yu Bezsudnova (Public Library of Science (PLoS), 2021)
Creating biocatalysts for (R)-selective amination effectively is highly desirable in organic synthesis. Despite noticeable progress in the engineering of (R)-amine activity in pyridoxal-5'-phosphate-dependent transaminases of fold type IV, the specialization of the activity is still an intuitive task, as there is poor understanding of sequence-structure-function relationships. In this study, we analyzed this relationship in transaminase from Thermobaculum terrenum, distinguished by expanded substrate specificity and activity in reactions with L-amino acids and (R)-(+)-1-phenylethylamine using α-ketoglutarate and pyruvate as amino acceptors. We performed site-directed mutagenesis to create a panel of the enzyme variants, which differ in the active site residues from the parent enzyme to a putative transaminase specific to (R)-primary amines. The variants were examined in the overall transamination reactions and half-reaction with (R)-(+)-1-phenylethylamine. A structural analysis of the most prominent variants revealed a spatial reorganization in the active sites, which caused changes in activity. Although the specialization to (R)-amine transaminase was not implemented, we succeeded in understanding the role of the particular active site residues in expanding substrate specificity of the enzyme. We showed that the specificity for (R)-(+)-1-phenylethylamine in transaminase from T. terrenum arises without sacrificing the specificity for L-amino acids and α-ketoglutarate and in consensus with it.